Fault Finding on Organizational Culture Based on Denison Model: A Case Study in Petroleum Industry Health Organization - Rahmani; Eftekhar; Saeedpour; Sharifi; Hojabri (Tehran University of Medical Sciences, 2014)
Abstract Background: This study attempts to review dimensions and indicators of organizational culture in Petroleum Industry Health Organizations utilizing Denison navigation framework and provide practical solutions to improve the situation based on strengths and weaknesses identification. Material and Methods: Thisapplied study was a descriptive - analytical one which performed using field assessment.Population study included all staffs of the organization's headquarters in Petroleum Industry Health Organization using systematic random sampling based on employeeslist and 110 staffs were selectedfinally. SurveyingOrganizational Culture Denison (DOCS, 2007) was used for data collectionin which the overall cultureOrganization and its characteristics and indicators were measured and the results compared with the global average. Results:The overall score of the corporate culture was in the middle status (2.8) and score of four maincharacters had fluctuation in the range 2.6 to 2.9. Fundamental values (3.1) had the most score and customer orientation (2.2) and development of capabilities (2.4) obtained the least scores in 12th indicators which these two indicators were identified as significant points to improve organizational culture. Conclusion:The scores revealed considerable distance with average global rates, but the scores are similar to other Iranian studies. The weakness of organizational culture in two indicators including "customer orientation" and "development of capabilities"can affect optimal organization performance through organization's compliance ability with environmental changes